TRAINING ON THE USE OF AVENZA MAP FOR THE MAPPING OF RICE-FIELD IN KECAMATAN GALING KABUPATEN SAMBAS - Buwono, Sri; Rustiyarso, Rustiyarso; Anasi, Putri Tipa; Ramadhan, Iwan; Christanto, Ludovicus Manditya Hari; Zatalini, Adhalia (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2024)
The training was carried out as a community service program that aimed to increase the skills of extension workers, village officials and peasants in Galing District, Sambas District, in mapping land for rice fields using the Avenza Map application. The background to this work stems from the urgent need for accurate, real-time information on agrarian land management, which is critical to promoting food security. Analysis of the situation has shown that many of the local growers and extension workers do not yet have the necessary skills to use modern mapping technologies, which hinders the efficiency and effectiveness of land management. The problems encountered include a lack of knowledge about mapping applications, as well as limitations in the acquisition and presentation of relevant data. The program, in part, provided training involving material delivery, question and answer sessions, and the practice of using Avenza Map. The training was designed to give the competitors practical knowledge and skills, so they could create job maps, input data, and present information in a geographic information system (SIG). This conclusion indicates that the training not only improves the skill of the participants, but also raises awareness of the importance of technology in modern farming. As the result, community service programs are expected to bring about a sustainable positive impact on rice field management in Kecamatan Galing, as well as encourage active community participation in utilizing technology to improve agricultural productivity.